1985
DOI: 10.1111/j.1151-2916.1985.tb10182.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Composite of Sic Whiskers in an MoSi2 Matrix

Abstract: A composite consisting of 20 vol% Sic whiskers in a hot-pressed MoSi, matrix was investigated. The composite displayed an =100% increase inflexural strength and a 54% improvement in fracture toughness, compared to the values measured for the matrix material. The improvements are attributed to the change in the microstructure of the MoSi2 afforded by the presence of the whiskers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(41 citation statements)
references
References 6 publications
1
38
0
2
Order By: Relevance
“…In the MoSi 2 binary composites SiC is found to raise significantly yield strengths and fracture toughness of MoSi 2 both at low and high temperature [3,5,6]. Although increased fracture toughness was achieved in SiC particle-reinforced MoSi 2 composites [6], the mechanical properties of SiC p /MoSi 2 are not as good as SiC w /MoSi 2.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the MoSi 2 binary composites SiC is found to raise significantly yield strengths and fracture toughness of MoSi 2 both at low and high temperature [3,5,6]. Although increased fracture toughness was achieved in SiC particle-reinforced MoSi 2 composites [6], the mechanical properties of SiC p /MoSi 2 are not as good as SiC w /MoSi 2.…”
Section: Introductionmentioning
confidence: 89%
“…To improve the mechanical properties of MoSi 2 , researchers have used second-phase reinforcements such as whiskers, particulates and platelets of various carbides, silicides and oxides, etc. [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…17 In this case the crack deviation mechanism at the SiC-MoSi 2 interface is said to be dominant. 18,19 It is also reported that there is a good thermodynamic compatibility between SiC and MoSi 2 . 18-20 Some researchers have tried to manufacture MoSi 2 /RBSC (reaction bonded silicon carbide) by infiltrating a SiC preform with liquid MoSi 2 .…”
Section: Introductionmentioning
confidence: 96%
“…• C. Hence, reinforcement of the matrix with thermally stable ceramic particles or whiskers which can significantly improve the fracture toughness at room temperature as well as high temperature properties is recommended [5][6][7]. It is chemically compatible with a number of ceramic constituents such as SiC, Si 3 N 4 , TiC, TiSi 2 , ZrO 2 , Al 2 O 3 , and so forth, which could be judicially selected as reinforcement for particular use and temperature regime [8,9].…”
Section: Introductionmentioning
confidence: 99%